Microfungi of Windmill Island, Antarctica: Diversity and ultrastructure studies of Soil Fungi - Omar, Suhaila; Alias, Siti Aisyah; Abdul Wahab, Azlina (Malaysian Journal of Science, 2009)
Soil materials were collected during two summer expeditions to the Windmill Island, Antarctic in 2002 and 2004 to determine occurrence and distribution of culturable fungi using a modified Warcup’s soil plate method. A total of 10 fungi consisting of eight species of Ascomycetes, one Zygomycete and one yeast were isolated. The most common species isolated from Windmill Island were Cadophora malorum, Geomyces cretaceous and Thelebolus microsporus while Aureobasidium sp., Antarctomyces sp., Mucor sp., Mrakia frigida, Trichosporiella cerebriformis, and Phoma sp. were less common. Ultrastructure studies of the fungi were also undertaken. This is the first report of Trichosporiella cerebriformis isolated from Continental Antarctic soils.